(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
Hospital network service is calculated This essay aims to comparatively analyze the technical efficiency of the network of hospital health, according SILAIS, using the technique of stochastic frontier. This technique consists of adjusting a production function using econometric techniques. The expected outcome is to have an efficiency measure for SILAIS of their respective hospital networks. For the application of stochastic frontier production function Cobb-Douglas to which is added noise disturbances (symmetric) and efficiency (half normal) and using the Stata program, the parameters of interest are estimated specified and efficiency for each. DOI: http://dx.doi.org/10.5377/reice.v2i4.1725 REICE Vol. 2, No. 4, julio-diciembre 2014: 49-56